Effect of Additives on the Properties of Different Types of Greases - A.R. Mohammed, Muhannad (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The aim of this research is to study the influence of additives on the properties of soap greases, such as lithium, calcium, sodium, lithium-calcium grease, by adding varies additives, such as graphite, molybdenum disulfide, carbon black, corrosion inhibitor, and extreme pressure. These additives have been added to grease to obtain the best percentages that improve the properties of grease such as load carrying, wear resistance, corrosion resistance, drop point, and penetration. The results showed the best weight percentages to all types of grease which give good properties are 1.5% extreme pressure additive, 3% graphite, 1% molybdenum disulfide, 2.5% carbon black. The other hand, the best weight percentage for corrosion inhibitor is 1% to lithium-calcium grease, 2% to lithium grease, and 3% to sodium grease. It was concluded that there is no need to add corrosion inhibitor to calcium grease